The Little Data Book 2003 - World Bank (World Development Indicators, 2003)
The Little Data Book, a pocket-sized ready reference, contains key development data for 208 countries. The Little Data Book 2003 provides profiles of each country with 54 development indicators including: Population and population growth. GNI, GDP growth, Exports and Imports, and Gross Capital Formation. Deforestation, Water Use, Energy Use and Electricity Use per Capita. Life Expectancy, Fertility Rate, Child Malnutrition, Prevalence of HIV, Girls in Primary School. Paved Roads, Aircraft Departures, Personal Computers. High-technology exports, Foreign Direct Investment, Present Value of Debt, and Aid per Capita. Drawing on data from the World Development Indicators 2003, The Little Data Book 2003 provides a quick reference to the latest available data for World Bank member countries as well as other economies with populations of over 30,000